An ultrasensitive and specific CRISPR-Cas13a-mediated point-of-care assay for monkeypox detection and PCR-based clade detection - Qin Zhang; Yan Yu; Bin Yin; Liang Xu; Hui Chen; Runjie Qiao; Ang Chen; Na Zhu; Xuping Wu (Infectious Diseases of Poverty)
Abstract Background The rapid increase in the number of monkeypox cases poses a considerable threat to the international community, necessitating sensitive, fast, and available diagnostic methods. Therefore, the objective of this study was to develop a rapid, sensitive and simple method with high clinical applicability. Methods We developed a simple, rapid point-of-care assay to detect monkeypox virus (MPXV) using multienzyme isothermal rapid amplification (MIRA) coupled with the clustered regularly interspaced short palindromic repeats (CRISPR)-Cas13a system. The detection system was optimized by synthesizing plasmids, and the detection sensitivity was explored by the continuous dilution of the plasmid. We validated the accuracy of this assay on 202 clinical MPXV samples and 104 interference samples through the kappa test. The visual interpretation of the results was realized by combining the assay with lateral flow strips. In addition, we developed a PCR-based method to identify MPXV Clades I and II, and the accuracy was tested through a kappa test on 202 clinical monkeypox samples and 104 interference samples. Results Our assay achieved an analytical sensitivity of 14.4 copies/ml and high selectivity, as it differentiated MPXV from three other Orthopoxvirus species. The clinical testing results for 202 monkeypox samples and 104 interference samples demonstrated 100% sensitivity and specificity. Compared with quantitative PCR (qPCR), three samples tested as positive using our assay, which showed that the performance of this assay was superior to that of the qPCR assay. Combined with lateral flow strips, its availability and simplicity provide an alternative point-of-care diagnostic method for MPXV testing in remote settings and resource-poor areas. The results of 32 clinical samples showed that lateral flow strips had a high detection sensitivity and could identify samples with Ct value of 39 as positive. The clade identification assay detected as few as 200 copies/ml within 40 min and no cross-reaction was observed between Clades I and II. The clinical samples tested were all Clade II, which was consistent with the circulating clade in the Chinese mainland. Conclusions The MIRA-CRISPR-Cas13a-MPXV system offers a rapid, sensitive and specific approach for monkeypox diagnosis, with significance for monitoring monkeypox epidemics. The clade identification assay based on PCR could accurately distinguish Clade I from Clade II within 40 min and can be implemented for high-throughput operation. Graphical abstract